2016
DOI: 10.1111/jre.12428
|View full text |Cite
|
Sign up to set email alerts
|

Influence of experimental periodontitis on cardiac oxidative stress in rats: a biochemical and histomorphometric study

Abstract: The pronounced increase in cardiac oxidative stress caused by periodontitis was due to an excessive increase in the production of reactive oxygen species, rather than due to decreased antioxidant capacity. The results indicate that periodontitis-related cardiac oxidative stress might be one of the mechanisms that contribute to the pathological process that leads to heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…They emphasized that increased oxidative stress in the presence of chronic periodontitis may cause endothelial dysfunction of the blood vasculature, predisposing to atherosclerotic plaque formation and increasing predisposition to ischemic heart disease [1]. Köse et al [52] examined the influences of periodontitis on levels of cardiac oxidative stress. Authors found that GSH-Px levels in the heart ventricular tissue of the rats with experimental periodontitis were higher than that of control group but statistically insignificant [52].…”
Section: Cardiovascular Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…They emphasized that increased oxidative stress in the presence of chronic periodontitis may cause endothelial dysfunction of the blood vasculature, predisposing to atherosclerotic plaque formation and increasing predisposition to ischemic heart disease [1]. Köse et al [52] examined the influences of periodontitis on levels of cardiac oxidative stress. Authors found that GSH-Px levels in the heart ventricular tissue of the rats with experimental periodontitis were higher than that of control group but statistically insignificant [52].…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…Köse et al [52] examined the influences of periodontitis on levels of cardiac oxidative stress. Authors found that GSH-Px levels in the heart ventricular tissue of the rats with experimental periodontitis were higher than that of control group but statistically insignificant [52]. They argued that this increase could be associated with adaptive response [52].…”
Section: Cardiovascular Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…18,19 Studies have proven MMPs, especially the MMP-9, to play a pivotal role in the pathogenesis of atherosclerosis, hypertension, myocardial infarction, and heart failure. 20 Experimental studies by our colleagues 3,21 and other researchers 12,22 showed that as a chronic low-level systemic inflammatory-oxidative disease, periodontitis causes significant inflammatory 3 and oxidative 12,21,22 changes in left ventricular tissue. Despite the well-known cardioprotective effect of melatonin, there is very limited information about its protective effects on periodontitis-related cardiac alterations.…”
Section: Introductionmentioning
confidence: 95%